Studi Bibliografi: Perkembangan Penelitian Kebijakan Dividen Pada Perusahaan Yang Terdaftar di Bursa Efek Indonesia - Fathony, Haris Reza; Aryani, Y. Anni; Setiawan, Doddy; Djuminah, Djuminah (Accounting Study Program, Faculty Economics and Business, Universitas Sebelas Maret, 2024)
This study aims at providing empirical evidence of research-development on dividend policy in Indonesia Stock Exchange. This study analyzes the dividend policy which consists of 32 articles from 19 nationally accredited journal (Sinta 1 and Sinta 2) taken from 2017 until 2022. The writers of this study do the classification based on the topic, finance variable and non finance variable. The method used in this study is